2019
DOI: 10.1002/aur.2079
|View full text |Cite
|
Sign up to set email alerts
|

Oral probiotic administration during pregnancy prevents autism‐related behaviors in offspring induced by maternal immune activation via anti‐inflammation in mice

Abstract: Maternal immune activation (MIA) is associated with an increased risk for autism spectrum disorders (ASD) in offspring. Animal experiments have found that interleukin 6 (IL‐6) and IL‐17a are key cytokines in the induction of ASD by MIA. Moreover, probiotics were verified to inhibit the production of proinflammatory cytokines. Therefore, we investigated whether the administration of oral probiotics during pregnancy might protect the offspring that have suffered MIA from developing ASD. Probiotics were orally ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
2
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(49 citation statements)
references
References 49 publications
1
38
2
1
Order By: Relevance
“…Several studies in the literature report the protective effect of the treatment with anti-inflammatory drugs on MIA models, but most of them have been performed on the offspring [ 31 , 84 , 85 , 86 , 87 ]. Only a few studies have been conducted on dams, but not using pharmacological treatment with anti-inflammatory drugs [ 88 , 89 , 90 , 91 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies in the literature report the protective effect of the treatment with anti-inflammatory drugs on MIA models, but most of them have been performed on the offspring [ 31 , 84 , 85 , 86 , 87 ]. Only a few studies have been conducted on dams, but not using pharmacological treatment with anti-inflammatory drugs [ 88 , 89 , 90 , 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the field of neuropsychiatry, the idea that alteration of minicolumnar cortical structure and function (minicolumnopathy) may be responsible for aberrant brain function is growing [ 66 , 70 , 92 ]. Minicolumns are basal and functional units of the brain cortex and minicolumnopathies are modifications of minicolumnar homeostasis induced by various factors, such as neuroinflammation, gene expression or environmental factors, typically present in several NDDs [ 89 , 90 , 91 , 92 ]. We demonstrated, for the first time, that LPS prenatal exposure induces aberrant brain cytoarchitecture.…”
Section: Discussionmentioning
confidence: 99%
“…In the same context, a study conducted by Wang et al showed that oral probiotic administration during pregnancy prevents autism-related behaviors in offspring. It has been shown in this study that the administration of 1.5675 × 10 7 cfu Bifidobacteria (B. bifidum and B. infantis) and 5.28 × 10 8 cfu Lactobacillus helveticus every 24 h for 21 days in addition to prebiotics (fructooligosaccharides (FOS) and maltodextrin) decreases the incidence of ASD in offspring and inhibits the production of proinflammatory interleukin 6 (IL-6) and IL-17a, which are key cytokines in the induction of ASD by maternal immune activation [165].…”
Section: Animal Studiesmentioning
confidence: 99%
“…A role for probiotics has been suggested for children with ASD as well, as preliminary findings from experimental animals studies provide some evidence that administration of selected probiotics may be effective in reducing neurologic signs and symptoms associated with gut dysbiosis. In a summary of studies to date, several probiotic strains, i.e., [18,[89][90][91][92]. In a mouse model of ASD induced by maternal immune activation, oral administration of human commensal B. fragilis corrected intestinal permeability, restored GM, improved GI physiology, and abolished ASD-like behavioral disruptions [18].…”
Section: Probioticsmentioning
confidence: 99%